2021
DOI: 10.1002/ecs2.3301
|View full text |Cite
|
Sign up to set email alerts
|

Reef‐wide evidence that the presence of sharks modifies behaviors of teleost mesopredators

Abstract: The idea that the presence of sharks impacts the behavior of mesopredatory reef fishes is controversial and lacks clear evidence at reef‐wide scales. We compared the abundance and behavior of these reef fishes in response to the presence of reef sharks using Baited Remote Underwater Video System (BRUVS) deployments in two adjacent reef systems where sharks have either been exclusively targeted by fishing or protected by a no‐take marine reserve. For a subset of videos, we also compared the behavior of mesopred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
(82 reference statements)
1
7
0
Order By: Relevance
“…Instead, our results support the recent evidence that metrics such as MaxN are not subtle enough to detect behavioural dynamics that occur over short time scales (i.e. seconds -minutes) (Coghlan et al 2017, Speed et al 2019, Lester et al 2021a). As a result, such metrics may be robust to any effect of the presence of both apex and reef sharks on the abundance of smaller fishes over long (i.e.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Instead, our results support the recent evidence that metrics such as MaxN are not subtle enough to detect behavioural dynamics that occur over short time scales (i.e. seconds -minutes) (Coghlan et al 2017, Speed et al 2019, Lester et al 2021a). As a result, such metrics may be robust to any effect of the presence of both apex and reef sharks on the abundance of smaller fishes over long (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Because sharks are highly mobile (Vianna et al 2013, Ferreira et al 2015, responses by mesopredators may only occur when larger predators/competitors appear in close proximity to the bait bag and when they are recognised as an immediate threat. Recent work by Lester et al (2021a) shows that this is likely to be the case -mesopredators showed significant antithreat behaviours on stereo-BRUV deployments immediately following the appearance of sharks. This analysis found that the response to predators was both species and context-specific, depending on the behaviour of both the mesopredator and the shark, and the amount of shelter offered by the reef Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, it is possible that C. cruentata on reefs with higher predation risk have larger diurnal home ranges to provide a range of refuges or maximize foraging opportunities outside of crepuscular periods when threats from transient predators are greater (Papastamatiou et al ., 2015). Because home ranges are established and develop over the lifespan of a fish, this result may provide further evidence of chronic responses of fishes to predation risk in addition to the more instantaneous acute responses to immediate risk (Lester et al ., 2021; Madin et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%